Kerentanan Schistosoma japonicum terhadap Praziquantel di Napu dan Lindu, Sulawesi Tengah Indonesia - Anis Nurwidiyati; Triwibowo AG; Phetisya PFS; Risti Risti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Schistosomiasis in Indonesia is found in Napu, Lindu and Bada highland, Central Sulawesi. This disease is caused by Trematode worm, Schistosoma japonicum. Mass chemotherapy using praziquantel was done to reduce the prevalence of schistosomiasis since 1980’s. The objective of this study was to identify the development of resistance in S. japonicum to praziquantel in endemic areas. Field study was conducted in endemic areas Napu and Lindu in April –November 2011. All of the 80 stool-positive subjects in Napu and 60 stool-positive subjects in Lindu, were treated with a single dose of 60 mg/kg of praziquantel. On three, six, nine, and 12 weeks after treatment, all of the subjects were e xamined again using the same stool examination. The results showed that on three weeks examination after treatment, stoolnegative results were found in all subjects which represents a 100 % parasitological cure rate. All stool samples were re-examined six, nine, and 12 weeks after the first treatment and no stool-positive subjects were found. The results indicate that there was no evidence for reduced susceptibility of S. japonicum to praziquantel despite its extensive use in the endemic areas of Napu and Lindu for more than 20 years.